Exploring Ideational Metafunction in Helon Habila's Oil On Water: A Re-evaluation and Redefinition of African Women's Personalit and Identity Through Literature - Koussouhon, Léonard (My University, 2015)
Abstract
Keywords: Systemic functional grammar; experiential meaning; re-evaluation; womanism; women's identity